The historic Lake Biwa Canal as a permanent catalyst for the development of Kyoto’s landscape architecture - G. Shevtsova (Architectural Studies, 2023)
The historic Lake Biwa Canal, an artificial waterway that supplies water from Lake Biwa to Kyoto, was built to revitalise Kyoto after the capital was moved to Tokyo in 1868. Apart from its main function, the canal plays a significant role in organising the cultural landscape of the surrounding areas. This study raised topical issues of sustainable development, preservation, and revitalisation of historic engineering structures. The artificial waterway was considered in terms of its pulling effects on the surrounding environment, both urban and landscape. The purpose of this study was to find the characteristics of the landscape-organising role of the Biwa Canal and its transformation over time, specifically with adaptation to the relevant problems of modern time. The study was conducted mainly using in situ field research methods. As a result, the key role of the canal as a constant catalyst for the development of Kyoto’s landscape architecture was outlined, which has changed substantially over time, but has not weakened and has always been innovative, organically combining modern industrial achievements with local traditions. In the first period of its existence (until 1951), the focus of landscape organising activities in the areas adjacent to the canal was on the creation of private and temple gardens, but from the second period of its existence (1951-early 1990s), the focus of landscape activities around the canal shifted to public recreational and park aspects. During the third period (since the early 1990s), when the canal was recognised as a National Historic Site, trends in the development of industrial and landscape tourism were also observed. The experience of preserving, revitalising, promoting, and adapting the landscape role of the Biwa Canal to the new needs of the present can be used as an example of the direction of similar activities for historic waterways in the world